SOME SALIENT CONTRIBUTIONS OF THE FABC TO THE ASIAN CHURCHES DURING THE PAST 40 YEARS - Tirimanna, Vimal (Asian Horizons, 2012)
As the Federation of Asian Bishops’ Conferences (FABC) chalks up the 40th year of its fruitful existence this year (2012), perhaps it is opportune to take stock of its service to the Asian Churches. With this in mind, in this article, I intend to reflect briefly on the unique service rendered by the FABC to the Asian Churches1 by highlighting a few salient characteristics of the FABC’s contribution to them, under the following sub-headings.